Changes in Utilization and Health Among Low-Income Adults After Medicaid Expansion or Expanded Private Insurance - Sommers, Benjamin D; Blendon, Robert J; Orav, E John; Epstein, Arnold M (JAMA internal medicine, 2016)
Under the Affordable Care Act (ACA), more than 30 states have expanded Medicaid, with some states choosing to expand private insurance instead (the "private option"). In addition, while coverage gains from the ACA's Medicaid expansion are well documented, impacts on utilization and health are unclear. To assess changes in access to care, utilization, and self-reported health among low-income adults in 3 states taking alternative approaches to the ACA. Differences-in-differences analysis of survey data from November 2013 through December 2015 of US citizens ages 19 to 64 years with incomes below 138% of the federal poverty level in Kentucky, Arkansas, and Texas (n = 8676). Data analysis was conducted between January and May 2016. Medicaid expansion in Kentucky and use of Medicaid funds to purchase private insurance for low-income adults in Arkansas (private option), compared with no expansion in Texas. Self-reported access to primary care, specialty care, and medications; affordability of care; outpatient, inpatient, and emergency utilization; receiving glucose and cholesterol testing, annual check-up, and care for chronic conditions; quality of care, depression score, and overall health. Among the 3 states included in the study, Arkansas (n=2890), Kentucky (n=2898, and Texas (n=2888), there were no differences in sex, income, or marital status. Respondents from Texas were younger, more urban, and disproportionately Latino compared with those in Arkansas and Kentucky. Significant changes in coverage and access were more apparent in 2015 than in 2014. By 2015, expansion was associated with a 22.7 percentage-point reduction in the uninsured rate compared with nonexpansion (P < .001). Expansion was associated with significantly increased access to primary care (12.1 percentage points; P < .001), fewer skipped medications due to cost (-11.6 percentage points; P < .001), reduced out-of-pocket spending (-29.5%; P = .02), reduced likelihood of emergency department visits (-6.0 percentage points, P = .04), and increased outpatient visits (0.69 visits per year; P = .04). Screening for diabetes (6.3 percentage points; P = .05), glucose testing among patients with diabetes (10.7 percentage points; P = .03), and regular care for chronic conditions (12.0 percentage points; P = .008) all increased significantly after expansion. Quality of care ratings improved significantly (-7.1 percentage points with "fair/poor quality of care"; P = .03), as did the share of adults reporting excellent health (4.8 percentage points; P = .04). Comparisons of Arkansas vs Kentucky showed increased private coverage in the former (21.7 percentage points; P < .001), increased Medicaid in the latter (21.3 percentage points; P  < .001), and higher diabetic glucose testing rates in Kentucky (11.6 percentage points; P = .04), but no other statistically significant differences. In the second year of expansion, Kentucky's Medicaid program and Arkansas's private option were associated with significant increases in outpatient utilization, preventive care, and improved health care quality; reductions in emergency department use; and improved self-reported health. Aside from the type of coverage obtained, outcomes were similar for nearly all other outcomes between the 2 states using alternative approaches to expansion.